Multisensor fusion and integration in the wake of big data, deep learning and cyber physical system : an edition of the selected papers from the 2017 IEEE International Conference on Multisensor Fusion and Integration for Intelligent Systems (MFI 2017) /: an edition of the selected papers from the 2017 IEEE International Conference on Multisensor Fusion and Integration for Intelligent Systems (MFI 2017). (2018) - Unknown
No abstract available